Hubungan Konten Promo Diskon dengan Keputusan Mengunduh Aplikasi Mobile Banking BRImo, MyBCA, dan Livin’ - Evelyn Purwaningsih; Amiruddin Saleh (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2026)
The popularity of digital marketing is increasing in line with changes in consumer habits, as more people utilize digital media engaging with digital services. One of the most widely used strategies in the digital era is discount-based promotions. This study aims to examine discount promotional content using Media Richness Theory; analyze consumer download decisions through the AISAS Model framework; and assess the correlation between discount-based promotional content with the decision to download mobile banking applications. The research employs both descriptive and inferential analytical methods. Descriptive analysis is utilized to summarize the questionnaire responses, while inferential analysis is conducted using the Spearman rank correlation test to evaluate the strength and direction of associations between variables. Data was processed using SPSS as the statistical analysis tool. The study sample comprised 157 respondents, selected through the Slovin sampling formula. Findings indicate that most respondents perceived the discount promotional content as high in media richness; most respondents exhibited high levels of intention in download behavior; and a statistically significant relationship was identified between discount-based promotional content and mobile banking application download decisions.